Analysis of the Institution's Duties Regulation in Article 58 of Law Number 27 of 2022 concerning Personal Data Protection - Enis Tristiana (MASI Mandiri Edukasi, 2026)
Personal data protection is one of the human rights that is part of personal personal protection, so it is necessary to be given a legal basis to provide security for personal data, based on the 1945 Constitution of the Republic of Indonesia. In addition, the protection of personal data is aimed at ensuring citizens' rights to personal self-protection and fostering public awareness as well as ensuring recognition and respect for the importance of personal data protection. However, the state in providing personal data protection for citizens needs to form an institution that can accommodate problems that arise or integrate data between institutions or bodies or materials with corporations that collect citizens' personal data. This is so that more rigid arrangements are needed related to the duties of institutions regulated in Article 58 of Law Number 27 of 2022 concerning Personal Data Protection